Rancang Bangun Sistem Informasi Pengendalian Persediaan Bahan Baku Dengan Menggunakan Metode Reorder Point pada CV. Cahaya Karya Tehnik - Asari, Riski Imam; Setyawan, Henry Bambang; Nurcahyawati, Vivine (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2014)
Abstract: Warehouse in CV. Cahaya Karya Tehnik have problems in controlling the supply of raw materials because it is still done by manual. This results in the process of reporting for incoming raw material, raw material, inventory mutations the raw material, and reorder filing supplies raw materials takes time which tend to be longer. Because of that is required application control the supply of raw materials that can be used to take note of raw materials in, mutations raw materials, and the submission of reserving reexamined raw materials, so that the supply of raw materials at warehouse CV. Cahaya Karya Tehnik can run well and no vacant supplies. System also can print form mutation raw material that can be used as an archive warehouse. With the implementation of this system, the warehouse is no longer experiencing the emptiness of supplies of raw materials. The resulting system is expected to address the existing problems so far, and the resulting information will be more accurate. Besides that part of the barn is CV. Cahaya Karya Tehnik can control the supply of raw materials that is in the barn.Keywords: Raw Materials, Mutations Raw Materials, Warehouse